Molecular research on the systematically challenging smoothhound shark genus Mustelus: a synthesis of the past 30 years. Issue 4 (2nd October 2017) - Maduna, SN; Bester-van der Merwe, AE
Abstract : The species-rich genus Mustelus (smoothhounds) of the shark family Triakidae is one of the most bio-economically important groups of elasmobranchs in the world's oceans. Despite the commercial value of Mustelus, the systematics of the group remains largely unresolved and there is no global review or synthesis of knowledge about the conservation status and conservation genetics of smoothhounds across all oceanic regions. Here, we analysed published studies as well as grey literature to gain insight into the biogeographic, ecological and behavioural factors that shape genetic diversity in smoothhounds, and we identify critical knowledge gaps. From a series of molecular phylogenetic studies it can be inferred that the genus Mustelus is paraphyletic and that the aplacental species evolved secondarily from the placental species of the genus. The increasing availability of genetic data aids in disentangling systematic issues, such that more meaningful morphological characters can be chosen for use in practical field-identification keys for co-occurring smoothhounds. An integrative taxonomic approach to the genus Mustelus may offer the best chance of recording and protecting the biodiversity of these sharks. Furthermore, it is evident that different smoothhound species exhibit unique gene-flow patterns, suggesting varying rates within species and hence that species-level conservation approaches would be most appropriate. Molecular studies have advanced our understanding of smoothhound biology (including reproductive traits), ecology and evolution. While many knowledge gaps remain, a crucial lesson from this review is that, when doing assessments on a molecular level, it is important to place genetic results in a broader context, by assimilating biological and ecological data, if definitive conclusions are to be drawn.